Aphid performance and population development on their host plants is affected by weed–crop interactions. Issue 5 (26th July 2013) - Dahlin, Iris; Ninkovic, Velemir
Summary: Some farming practices, like organic farming, lead to greater numbers of weed plants in crop fields. These fields may give us some insights into any benefits that may be gained from biodiversity (e.g. improved pest control services) and allow us to understand the mechanisms behind crop–weed interactions. The influence of two common weeds, lamb's‐quarters Chenopodium album and charlock Sinapis arvensis, on performance of the bird cherry‐oat aphid Rhopalosiphum padi in spring‐sown barley Hordeum vulgare is evaluated in three field experiments. Observations in field experiments indicated that the presence of S. arvensis reduced aphid population development in the barley crop significantly, but this effect was not observed in barley grown with C. album . Observed effects in the field were further studied in laboratory experiments with regard to aphid growth and reproductive performance. Above‐ and below‐ground interactions of S. arvensis and C. album with barley were tested using twin‐exposure cages. Aphid performance was negatively affected when barley plants had root contact with S. arvensis . The results of these laboratory experiments showed a difference in mode of action of the two weeds. Synthesis and applications . The results support the potential of associated resistance, mediated by neighbouring plants, in minimizing herbivore damage of focal plants and highlighted the mechanism by which herbivores might be affected. Since chemical exchange between plant neighbours can potentially occur in any plant community, increased understanding could be valuable for existing and new agroecosystems, invasion biology and sustainable crop production. To get a balance between herbicide and insecticide control, agricultural production systems need to focus on the thresholds of weed and insect tolerance, taking the associated resistance of biodiversity (here weeds) into account. Agricultural biodiversity may provide many long‐term benefits over monoculture, from reducing pesticide pollution to preventing insecticide resistance. Our study is an important step forward in general understanding of the effects of vegetational diversity on herbivore population dynamics. Abstract : The results support the potential of associated resistance, mediated by neighbouring plants, in minimizing herbivore damage of focal plants and highlighted the mechanism by which herbivores might be affected. Since chemical exchange between plant neighbours can potentially occur in any plant community, increased understanding could be valuable for existing and new agroecosystems, invasion biology and sustainable crop production. To get a balance between herbicide and insecticide control, agricultural production systems need to focus on the thresholds of weed and insect tolerance, taking the associated resistance of biodiversity (here weeds) into account. Agricultural biodiversity may provide many long‐term benefits over monoculture, from reducing pesticide pollution to preventing insecticide resistance. Our study is an important step forward in general understanding of the effects of vegetational diversity on herbivore population dynamics.